Dielectric study of Clove oil - Satyendra Pratap Singh (Journal of Ayurveda and Integrative Medicine, 2018)
Dielectric properties of clove oil were determined using an impedance gain phase analyzer (HP 4194 A) at discrete frequencies between 10 kHz and 3 MHz and a range of temperature between 25 °C and 45 °C. A micro processor controller based temperature controller (Julabo F-25) was used for keeping the temperature of clove oil constant. Dielectric constant of the sample is found to decrease with increase in frequency and temperature, while dielectric loss decreases with increase in frequency but increases with increase in temperature. Penetration depth has been calculated with the help of dielectric data and is found to decrease with increase in frequency. Keywords: Dielectric constant, Dielectric loss, Penetration depth, Clove oil